trans-dominant mutants of E1A provide genetic evidence that the zinc finger of the trans-activating domain binds a transcription factor. - Webster, L C (1991)
The 289R E1A protein of adenovirus stimulates transcription of early viral and certain cellular genes. trans-Activation requires residues 140 to 188, which encompass a zinc finger. Several studies have indicated that trans-activation by E1A is mediated through cellular transcription factors. In particular, the ability of the trans-dominant E1A point mutant hr5 (Ser-185 to Asn) to inhibit wild-type E1A trans-activation was proposed to result from the sequestration of a cellular factor. Using site-directed mutagenesis, we individually replaced every residue within and flanking the trans-activating domain with a conservative amino acid, revealing 16 critical residues. Six of the individual substitutions lying in a contiguous stretch C terminal to the zinc finger (carboxyl region183-188) imparted a trans-dominant phenotype. trans-Dominance was even produced by deletion of the entire carboxyl region183-188. Conversely, an intact finger region147-177 was absolutely required for trans-dominance, since second-site substitution of every critical residue in this region abrogated the trans-dominant phenotype of the hr5 protein. These data indicate that the finger region147-177 bind a limiting cellular transcription factor and that the carboxyl region183-188 provides a separate and essential function. In addition, we show that four negatively charged residues within the trans-activating domain do not comprise a distinct acidic activating region. We present a model in which the trans-activating domain of E1A binds to two different cellular protein targets through the finger and carboxyl regions.